Evaluasi Pelaksanaan Praktik Kerja Lapangan dalam Kurikulum Merdeka dan Implikasinya Terhadap Kesiapan Karir Murid SMK - Yulia Fransiska; Ambiyar Ambiyar; Hasan Maksum (Pusdikra-Publishing.com, 2026)
Vocational education plays a strategic role in preparing graduates with both technical competencies and career readiness to meet the evolving demands of industry and the labor market. Within the Merdeka Curriculum, the Industrial Internship Program (Praktik Kerja Lapangan/PKL) has been implemented as an experiential learning approach that provides students with authentic workplace experiences. However, its effectiveness in fostering career readiness requires comprehensive evaluation. This study aimed to evaluate the implementation of PKL and examine its implications for the career readiness of vocational high school students. A descriptive quantitative approach was employed using survey methods supported by field observations. Data were collected through questionnaires and structured observations involving twelfth-grade students who had completed the internship program. The evaluation was conducted using the Context, Input, Process, and Product (CIPP) model, while career readiness was assessed through career planning, career exploration, self-efficacy, adaptability, communication, and collaboration indicators. The findings revealed that the implementation of PKL was categorized as good across all CIPP dimensions, with Context, Input, Process, and Product scores of 84.3%, 81.7%, 79.8%, and 86.5%, respectively. Students also demonstrated high to very high levels of career readiness. The results suggest that the effectiveness of PKL is influenced by program planning, the relevance of industry placements, mentoring quality, and students’ learning experiences. Therefore, PKL contributes significantly to strengthening career readiness and enhancing the alignment between vocational education and industry needs.